Impact of Early Antipsychotic Prescription Choice on Weight Gain in the First 5 Years of Psychotic Illness: a Retrospective Cohort Study - Adrian Heald; George Tilston; John Julian Warner-Levy; Loren Wilkins; Richard Williams; Toby Pillinger; William Deakin; Damien Longson; Lamiece Hassan; Caroline Dalton; Gavin P. Reynolds; Joseph Firth (Neurology and Therapy)
Abstract Introduction We analysed the effects of antipsychotic drug prescribing in year 1 of treatment for psychosis on future weight gain over 5 years. Methods We studied how weight changed over 5 years after the first diagnosis of psychosis/schizophrenia/schizoaffective disorder/delusional disorder/affective psychosis in 17,570 individuals and investigated its association with antipsychotic drug treatments prescribed in year 1 following diagnosis, over 30 years. Results The majority (65%) were aged 20–59 years at the time of first antipsychotic prescription. Mean baseline body-mass-Index (BMI) was similar in women versus men. Substantial increases in BMI were observed, with the greatest categorical changes seen in the obese (BMI ≥ 30 kg/m2) subjects, increasing from 30 to 43% for women and from 26% to 39% for men, while 42% of people did not significantly increase their weight. Individuals prescribed perphenazine/fluphenazine/amisulpride were most likely to remain at normal-BMI, while individuals prescribed aripiprazole/quetiapine/olanzapine/risperidone in the first year were most likely to gain weight/transition to overweight (25.0–29.9 kg/m2)/obese (≥ 30.0 kg/m2) from a normal BMI. The ‘typical’ agents thioridazine/chlorpromazine/flupenthixol/trifluoperazine/haloperidol were associated with an intermediate likelihood of BMI category change. In multivariate linear regression, factors associated with weight-gain were younger age/female sex(both p < 0.001), number of antipsychotic agents prescribed in 1st year (p < 0.001), plus specific agents aripiprazole (including 75% co-prescription or as 2nd line/3rd line)/olanzapine/thioridazine (p < 0.001), risperidone/quetiapine (p < 0.05). In multivariate logistic regression (weight increase ≥ 7%), the specific medication factors were similar, with odds ratios(OR) for specific medications ranging from quetiapine 1.09 (CI 1.00–1.21) to thioridazine 1.45 (CI 1.20–1.74). Conclusion Younger women were at elevated risk for weight gain as were people prescribed multiple antipsychotics in the 1st year. Some older antipsychotics associated with as much weight gain as the newer prescribed agents. More than 40% of people did not put on weight.